ANTIBIOTIKA, RESISTENSI, DAN RASIONALITAS TERAPI - Eka Rahayu Utami (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2011)
Bacterial resistance toward antibiotics has become international and serious problem. Rasional therapy campaign has common recently, include correct medication, precise dose, fix therapy periode and efficient cost. Microbes being resistance through some different ways for live survival. Many things can cause this resistance. In the end, there are a lot of harmful consequences in health, economic, also public health aspect. Rational therapy, government regulation, and civil education become some crusial point in bacterial resistance conquer strategy.Keywords: antibiotics, resistance, rational therapy.